OsCOL16, encoding a CONSTANS-like protein, represses flowering by up-regulating Ghd7 expression in rice. (July 2017) - Wu, Weixun; Zheng, Xiao-Ming; Chen, Daibo; Zhang, Yingxin; Ma, Weiwei; Zhang, Huan; Sun, Lianping; Yang, Zhengfu; Zhao, Chunde; Zhan, Xiaodeng; Shen, Xihong; Yu, Ping; et al.
Highlights: OsCOL16 encodes a group-II CO-like protein that delays heading and increases plant height and grain yield. Overexpression of OsCOL16 resulted in late flowering under both long-day and short-day conditions. OsCOL16 expression exhibits a diurnal oscillation and served as a transcription factor with transcriptional activation activity. OsCOL16 up-regulates the expression of the floral repressor Ghd7, leading to down-regulation of the expression of Ehd1, Hd3a, and RFT1 . Genetic diversity and evolutionary analyses suggest that remarkable differences in flowering times correlate with two major alleles of OsCOL16 . Abstract: Flowering time is an important agronomic trait that coordinates the plant life cycle with regional adaptability and thereby impacts yield potentials for cereal crops. The CONSTANS ( CO )-like gene family plays vital roles in the regulation of flowering time. CO-like proteins are typically divided into four phylogenetic groups in rice. Several genes from groups I, III, and IV have been functionally characterized, though little is known about the genes of group II in rice. We report the functional characterization in rice of a constitutive floral inhibitor, OsCOL16, encoding a group-II CO-like protein that delays flowering time and increases plant height and grain yield. Overexpression of OsCOL16 resulted in late heading under both long-day and short-day conditions. OsCOL16 expression exhibits a diurnal oscillation and serves as a transcription factor with transcriptional activation activity. We determined that OsCOL16 up-regulates the expression of the floral repressor Ghd7, leading to down-regulation of the expression of Ehd1, Hd3a, and RFT1 . Moreover, genetic diversity and evolutionary analyses suggest that remarkable differences in flowering times correlate with two major alleles of OsCOL16 . Our combined molecular biology and phylogeographic analyses revealed that OsCOL16 plays an important role in regulating rice photoperiodic flowering, allowing for environmental adaptation of rice.